Oxidative stress in neonates with hyperbilirubinemia before and after phototherapy: malondialdehyde and catalase activity - Putu Junara Putra; Rinawati Rohsiswatmo; Pustika Amalia Wahidiyat (Indonesian Pediatric Society, 2018)
Background Phototherapy is used to treat neonatal hyperbilirubinemia, but is currently thought to cause photodynamic stress and can induce lipid peroxidation. There is increasing evidence that many severe diseases of the neonates are caused by oxidative injury and lipid peroxidation. In the present communique, we review the oxidative succeptibility of the neonate and the evidence now available that phototherapy induces oxidative stress. Malondialdehyde (MDA) is a metabolic product of free radicals. Catalase is a antioxidant that binds free radicals. Objective To compare the levels of oxidants and antioxidants before and after phototherapy in neonates with hyperbilirubinemia. Methods This pretest-posttest control group study was conducted in Sanglah Hospital, Bali from November 2016 to April 2017. Thirty babies with gestational age â‰¥35 weeks and hyperbilirubinemia with total bilirubin levels requiring phototherapy were included in this study. The MDA levels and catalase activity were measured before and after 24 hours of phototherapy. Results Comparative analysis using paired T-test showed a significant increase of malondialdehyde level, with mean MDA 23.73 (SD 8.20) nmol/mL before and 53.05 (SD 10.18) nmol/mL after phototherapy (P<0.001). However, catalase activity significantly decreased from of 72.33 (SD 10.63) kU/L before phototherapy to 44.85 (SD 14.79) kU/L after phototherapy (P<0.001). The MDA level had a significant, negative association with catalase activity after phototherapy (r =-0.4; P=0.028). Conclusion Neonates with hyperbilirubinemia are found to have increased oxidative stress after phototherapy, as indicated by increased MDA levels and decreased CAT activity after 24 hours of phototherapy.